Pengembangan Lembar Kerja Peserta Didik Berbasis Discovery Learning dengan Pendekatan Saintifik pada Materi Struktur dan Fungsi Tumbuhan - Anggarwati, Melania Gisella; Ningsih, Kurnia; Titin (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
The purpose of this study is to develop and evaluate the efficacy of the student worksheet based on discovery learning and a scientific approach to the material structure and function of plants. The employed research method is Borg and Gall development research, which consists of five stages: research and information gathering, planning, product development, product testing, and product revision. The instruments for research were LKPD validation sheets and multiple-choice tests. CVR and CVI values of 1.00 indicated that discovery-based learning worksheets with a scientific approach were valid and suitable for use as instructional materials. Based on the results of the effect size test calculation, a student worksheet based on discovery learning and a scientific approach developed has an effectiveness value of 3.60 in the strong category. This demonstrates the use of discovery-based learning worksheets with a scientific approach contributing 99.98% of the learning outcomes of 34 students in class VIII E at SMPN 14 Pontianak regarding the structure and function of plants